The relationship between emotional intelligence, leadership styles, and burnout in NCAA coaches - Ugrenovic, L.; Shaffer, K. (The Sport Journal, 2020)
Burnout in coaches has been a concerning issue for many years. It can lead to a host of medical, psychological, emotional and performance-related issues. One of the many factors that correlates with burnout is emotional intelligence (EI; 22). Additionally, research supports various leadership styles that correlate with perceived burnout in different ways (32). The present study aimed to investigate the relationships between EI, leadership styles, and perceived burnout as well as the moderating role of leadership styles on the relationship between EI and perceived burnout in NCAA coaches. The full range leadership model (2) was used in this study and proposes that there are transformational, transactional, and passive-avoidant leadership styles. A total of 244 (n = 140 male, n = 103 female, n = 1 undisclosed) coaches participated from across all three NCAA divisions. Represented sports were field/cross country, basketball, lacrosse, soccer, swimming, volleyball, and a variety of others. Consistent with previous research, the results indicated a significant moderate negative relationship between EI and perceived burnout (r = -.38, p = .000) as well as a significant weak negative relationship between transformational leadership style and perceived burnout (r = -.24, p = .000). Additionally, there was a significant weak positive relationship between passive-avoidant leadership style and perceived burnout (r = .25, p = .000). Furthermore, passive-avoidant leadership style showed a negative moderating effect on the relationship between EI and perceived burnout, accounting for 20% of the variance in perceived burnout. This means that passive-avoidant leadership weakened the negative relationship between EI and perceived burnout. Thus, coaches who are predominately passive-avoidant leaders may be more likely to experience burnout symptoms despite their high EI. Consequently, the results underline the importance of developing strong leadership competences as well as EI in NCAA coaches to decrease or even prevent burnout.